AN EARLY PRESENTATION OF SUPRAGLOTTIC LARYNGEAL PARAGANGLIOMA: CASE REPORT AND REVIEW OF LITERATURE - Zaidi, Syed Aizaz Hussain; Raza, Syed Shahmeer; Ahmad, Danial; Medhat, Naila; Haq, Ihtisham Ul; Ayaz, Tayyaba; Ullah, Irfan; Khan, Muhammad Babar (Journal of Ayub Medical College Abbottabad, 2021)
A thirty-year-old male presented with progressive hoarseness and dysphagia for solids. Fibre optic laryngoscopy showed a right supraglottic mass. Subsequent CT imaging showed the location and extent of the mass. Biopsy revealed a Paraganglioma with cytokeratin negative and chromogranin positive cells. The mass was subsequently removed without complications. Follow up also showed no complications. Hoarseness and dysphagia resolved following tumour excision.